Management and Outcomes of Patients on Preoperative Plavix (Clopidogrel) Undergoing General Thoracic Surgery - Paul, Subroto; Stock, Cameron; Chiu, Ya-lin; Kansler, Amanda; Port, Jeffrey L.; Lee, Paul C.; Stiles, Brendon M.; Nasar, Abu; Sedrakyan, Art; Altorki, Nasser K. (The Thoracic and Cardiovascular Surgeon, 2013)
Objectives Plavix (clopidogrel) is a potent antiplatelet agent used to prevent thrombosis in a variety of clinical settings. The perioperative management of thoracic surgery patients who are on clopidogrel at the time of surgery is not well defined. We conducted this review to examine the perioperative management and outcomes of patients undergoing general thoracic surgical procedures.Methods From January 2005 to January 2010, 165 patients on clopidogrel underwent 182 operative procedures. Three management strategies were identified: Group I: clopidogrel continued through surgery (n = 17), Group II: clopidogrel discontinued with a bridging agent (n = 44) and Group III clopidogrel discontinued without a bridging agent (n = 121). Propensity score matched cohorts (17 clopidogrel continued; 34 clopidogrel discontinued) were constructed based on age, clopidogrel indication, American Society of Anesthesiology status, and procedure and used to compare the impact of clopidogrel management on postoperative bleeding and cardiovascular morbidity.Results Unmatched analysis revealed a significantly higher rate of transfusion in the group of patients who continued on clopidogrel throughout the perioperative period, compared with patients who had clopidogrel discontinued. Although there were more cardiovascular events in Groups II and III, there were no significant differences between groups in postoperative mortality, myocardial infarction, stroke, or reoperation for bleeding. In propensity matched patients only the rate of postoperative transfusions was significantly higher in patients continued on clopidogrel compared with patients whose clopidogrel was discontinued (35.3 vs. 2.9%), p < 0.004.Conclusions In selected patients, some thoracic surgical procedures can be performed safely on clopidogrel but are associated with higher rates of postoperative transfusion.
Keywords: antiplatelet therapy; thoracic surgery; clopidogrel